POLAR TRANSPORTATION EQUIPMENT - TESTS ON A MODEL 4VL TRACKMASTER - Pierce, N. E.; Moser, E. H. (1964)
A 7-passenger Model 4VL Trackmaster was tested on hard snow, sea ice, tundra, permafrost, sand and gravel in the Point Barrow, Alaska, area between January 1960 and October 1962. In 360 hours of testing, the vehicle was used intermittently to haul passengers and tow an Army Weasel sled loaded with one-ton of cargo. During the tests, it was found that small grousers on the track cleats improved turning characteristics on hard snow and smooth sea ice. It was also found that some mechanical redesign was required to improve reliability and ruggedness for all season use in polar areas. It was concluded that the Trackmaster appears promising as a general purpose vehicle for transporting personnel and light cargo in polar regions. (Author)